Free Space Optical Communication - Kaushal, Hemani; Jain, V.K; Kar, Subrat (Optical Networks, From Physical Layer to Service Offerings,, 2017)
This book provides an in-depth understanding of free space optical (FSO) communication with a particular emphasis on optical beam propagation through atmospheric turbulence. The book is structured in such a way that it provides a basic framework for the beginners and also gives a concise description from a designer's perspective. The book provides an exposure to FSO technology, fundamental limitations, design methodologies, system trade-offs, acquisition, tracking and pointing (ATP) techniques and link-feasibility analysis. The contents of this book will be of interest to professionals and researchers alike. The book may also be used as a textbook for engineering coursework and professional training.